A bit of statistics: Just one in millions - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Amid all the flurry about organic agriculture, just how much land is dedicated to this version of sound farming? Well, it depends on the definition but according to an extensive survey by the German-based Ecology and Agriculture Foundation....